2003
DOI: 10.1097/00042752-200303000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Worksite Physical Activity Programs on Physical Activity, Physical Fitness, and Health

Abstract: To increase the level of physical activity and to reduce the risk of musculoskeletal disorders, we support implementation of worksite physical activity programs. For the other outcome measures, scientific evidence of the effectiveness of such a program is still limited or inconclusive, which is mainly the result of the small number of high-quality trials. Therefore, we recommend performing more randomized, controlled trials of high methodological quality, taking into account criteria such as randomization, bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
226
2
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(256 citation statements)
references
References 45 publications
6
226
2
18
Order By: Relevance
“…We consider this increase to be clinically relevant in this population because of their low baseline cardiorespiratory fitness [24.9 (SE 6.6) ml O 2 × min -1 × kg -1 ] and because their aerobic workload already exceeded recommended levels. Previous worksite interventions have found similar effect sizes on cardiorespiratory fitness in both sedentary and physically demanding jobs (20,21).…”
Section: Primary Outcomementioning
confidence: 75%
See 1 more Smart Citation
“…We consider this increase to be clinically relevant in this population because of their low baseline cardiorespiratory fitness [24.9 (SE 6.6) ml O 2 × min -1 × kg -1 ] and because their aerobic workload already exceeded recommended levels. Previous worksite interventions have found similar effect sizes on cardiorespiratory fitness in both sedentary and physically demanding jobs (20,21).…”
Section: Primary Outcomementioning
confidence: 75%
“…To our knowledge, a reduction of the relative aerobic workload by aerobic exercise has not yet been shown to be successful among blue-collar workers. High quality aerobic exercise interventions among workers with high levels of occupational physical activity are few and with conflicting findings (16)(17)(18)(19), especially regarding cardiovascular risk factors such as cardiorespiratory fitness and blood pressure (BP) (20,21).…”
Section: Korshøj Et Almentioning
confidence: 99%
“…29,31 Some studies suggest that ergonomic advice on improving physical activity should be offered before the individual begins his or her working career or during education. 32,33 A study from Peros et al 34 showed that the introduction of a physical fitness program into the dental curriculum, involving 90 minutes of cardiovascular activity per week, had a positive impact on lower back pain amongst final-year dental students in Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…These chronic diseases reduce the sustainable working status in those with good health and contribute to early retirement. There is strong evidence from the Worksite Physical Activity Programs (WPAP) that an increase in workers' physical activity and general health is linked to a reduction in musculoskeletal disorders 29) . Because musculoskeletal disorders are one of the most common problems in the workplace that contribute to a reduced sustainable working status, preventing these disorders could help workers to sustain their jobs 30) or find other jobs, hence sustaining their working status following involuntary retirement.…”
Section: Discussionmentioning
confidence: 99%